Strata-bound tourmaline in the Archaean Malene supracrustals, West Greenland - Appel, Peter W. Uitterdijk (Canadian Journal of Earth Sciences, 1985)
Thin tourmaline-rich layers closely associated with strata-bound tungsten mineralization occur in layered amphibolites and metasediments of the Archaean Malene supracrustals in West Greenland. Locally, tourmaline is intergrown with scheelite. Microprobe analyses showed that the tourmaline is of intermediate composition, between schorl and dravite, with small variations in composition in different layers. The tourmaline is interpreted as being of submarine exhalative origin.